Tourist Preferences on Bunaken Island for Integrated Archipelagic Tourism Development around the Bunaken National Park, Indonesia - LAGARENSE, Bet El Silisna; WALANSENDOW, Agustinus (Journal of Environmental Management and Tourism; Vol 11 No 4 (2020): JEMT Volume XI Issue 4(44) Summer 2020, 2020)
This study aims at analyzing the preferences of tourists visiting Bunaken Island for the development of archipelagic tourism. Qualitative method was applied, and survey was done by distributing questionnaires to 200 tourists visiting the island. The tourist preferences-based island tourism development on Bunaken Island was very strategic for the development of integrated archipelagic tourism by building a network of relevant strategic tourism objects and attractions in other four islands (Siladen, Manado Tua, Mantehage and Nain) around the Bunaken National Park. The findings are very useful for public policy makers to enhance parthnership and empower communities in developing archipelagic tourism.